The Populus ARBORKNOX1 homeodomain transcription factor regulates woody growth through binding to evolutionarily conserved target genes of diverse function - Liu, Lijun (The New phytologist, 2015)
No claim to original US Government works. New Phytologist © 2014 New Phytologist Trust.